Strategies for Recruiting and Retaining Nurses for Rural Hospital Closure Research - Jessica G. Smith; Kyrah K. Brown; Melynda Hutchings; Elizabeth I. Merwin (Rural Nurse Organization; Binghamton University, 2021)
Purpose: Rural hospital closures result in the loss of lifesaving acute care for rural residents and threaten the health of rural communities significantly. Understanding short- and longer-term effects nurses experiences related to a rural hospital closure can pose a unique challenge, as nurses may relocate and become difficult to identify. In this paper, the authors describe the strategies used during a pandemic to recruit and retain rural nurse research participants who experienced a rural hospital closure. Strategies presented may help nurse researchers recruit a unique and difficult-to-reach rural nurse population during a pandemic. Sample: The sample consisted of nurses who worked in a rural hospital that closed between 2014 to 2020 in one Southwestern state. Method:  The authors describe multiple strategies used to recruit rural nurses such as public outreach, social media outreach, and personal outreach. Public outreach was used through professional organization email listservs and printed newspaper advertisements. Social media outreach included public posts online. Personal outreach to former rural hospital employees who were existing contacts was through personal social media messages, phone calls, and texts. Findings: The most effective method for recruitment and retention was personal outreach through rural hospital champions who sent personal messages using social media. The final sample included 10 nurses from two rural hospitals that closed. Five nurses reported about a hospital that closed in 2014, while five nurses reported about a hospital that closed in 2015. Conclusion: For successful recruitment, future researchers should use a direct, personal recruitment strategy to recruit and retain rural nurse research participants for studies about rural hospital closures. Other strategies for successful rural nurse recruitment for research include planning for an extended recruitment timeline, being flexible with participants regarding data collection procedures, cultivating research interest among rural nurses, and building a culture of research in rural settings. Keywords: rural, nursing, research, sampling, recruitment, hospital closure, COVID-19 DOI:  https://doi.org/10.14574/ojrnhc.v21i2.682  Acknowledgements: Our study was supported by the Excellence in Research Award sponsored by the Texas Organization of Baccalaureate and Graduate Nursing Education (TOBGNE)